Role Of Video as A Teaching Media to Improve Students’ Listening Skills - Lokanita, Ni Komang Tri; Rismadewi, Ni Wayan Monik; Dewi, Luh Mila Trisna (The Art of Teaching English as a Foreign Language (TATEFL), 2020)
The objective of this research is to find out the role of video as a teaching media to improve students’ listening skill and to describe how the use of video as a teaching media influences students’ motivation during the listening class. The research design of this study is library research or content analysis. The subjects of this research were 5 researches document. The total number of participants in this research was from 166 students. The results of the five researches that have been gathered by the writer showed that video as a teaching media plays important role for students’ listening skills. The roles of video as a teaching media to improve students’ listening skills are: 1) Video made the students became active in the teaching and learning process, 2) Video made the students became enthusiastic to join the listening class, 3) Video made the learning process became more fun, 4) Video could grab students’ attention, and 5) Video could motivate the students to join the listening class. The result of 5 researches showed that students improved their listening skills after being taught by using video.